Suprachiasmatic Nucleus and Subordinate Brain Oscillators: Clock Gene Desynchronization by Neuroinflammation - Campos, Leila Maria Guissoni [UNESP]; Buchaim, Rogerio Leone; Da Silva, Nathani Cristina [UNESP]; Spilla, Caio Sergio Galina; Hataka, Alessandre [UNESP]; Pinato, Luciana [UNESP] (Karger Publishers, 2018)
Objective: The clock genes Period (per) 1 and 2 are essential components in the generation and adjustment of biological circadian rhythms by the suprachiasmatic nucleus (SCN). Both genes are also rhythmically present in extrahypothalamic areas such as the hippocampus and cerebellum, considered subordinate oscillators. Several pathological conditions alter rhythmic biological phenomena, but the mechanisms behind these changes involving the clock genes are not well defined. The current study investigated changes in PER1 and PER2 immunoreactivity in the SCN, hippocampus, and cerebellum in a neuroinflammation model. Methods: Wistar rats received lipopolysaccharide (LPS) or vehicle intracerebroventricularly. The melatonin plasmatic content was quantified by ELISA to confirm the alterations in biological rhythms, and PER1 and PER2 immunoreactivities were analyzed in brain sections by immunohistochemistry. Results: In the SCN, intracerebroventricular LPS changed PER1 expression, increasing the number of PER1-immunoreactive (IR) cells at zeitgeber time (ZT) 15, decreasing it at ZT5 and ZT20 and not changing it at ZT10. LPS also induced a decrease in PER2-IR cells at ZT5, ZT10, and ZT15 but not at ZT20 in the SCN. In the hippocampus, LPS induced a decrease in PER1-IR and PER2-IR cells at both ZTs (ZT10 and ZT15). In the cerebellum, LPS increased the number of PER1-IR cells at ZT10 and decreased it at ZT15, while the number of PER2-IR cells was reduced at both ZTs. Conclusions: These results indicate that a neuroinflammatory condition leads to desynchronization of primary and subordinate brain oscillators, supporting the existence of the integration between the immune and the circadian system.
Keywords: Circadian rhythms; Clock genes; Neuroinflammation; Oscillators